ANALISIS PENGARUH PRODUK, PROMOSI DAN FASILITAS TERHADAP VOLUME PENJUALAN (Studi Kasus Di Toko Roti AAN Ungaran) - Imas Siti Bianca Faula Agoestian; Nurmiyati Nurmiyati; Pitaloka Dharma Ayu (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2023)
AAN Bakery is one of the trading businesses engaged in the food business, namely bread. The development of the ANN Bakery which is stagnant or less developed than other bakeries is suspected because it is caused by a product that lacks many choices of variants so that consumers feel bored with the choice of products that do not change, the promotions that are run are not well-targeted and facilities in the store is incomplete so that it affects the sales volume at the AAN Bakery. This study aims to determine and analyze the effect of products, promotions, and facilities at AAN Bakery. This study uses a quantitative method with a sampling technique using purposive sampling with a total sample of 96 respondents referring to the Roscoe formula and processed by SPSS version 25.The results showed that the product had an effect on sales volume with the results of the calculation of the value of tcount 4.256 > ttable 1.986, the promotion had no effect on sales volume with the calculated value of tcount 0.456 < ttable 1.986, facilities had an effect on sales volume with the calculated value of tcount 3.742 > ttable 1.986. While the results of simultaneous testing of products, promotions, and facilities together have an influence on sales volume with the results of the calculation of the value of Fcount 22.612 > Ftable 2.70.